Effectiveness of an electronic patient-centred self-management tool for gout sufferers: a cluster randomised controlled trial protocol. Issue 10 (16th October 2017) - Day, Richard O; Frensham, Lauren J; Nguyen, Amy D; Baysari, Melissa T; Aung, Eindra; Lau, Annie Y S; Zwar, Nicholas; Reath, Jennifer; Laba, Tracey; Li, Ling; McLachlan, Andrew; Runciman, William B; et al.
Abstract : Introduction: Gout is increasing despite effective therapies to lower serum urate concentrations to 0.36 mmol/L or less, which, if sustained, significantly reduces acute attacks of gout. Adherence to urate-lowering therapy (ULT) is poor, with rates of less than 50% 1 year after initiation of ULT. Attempts to increase adherence in gout patients have been disappointing. We aim to evaluate the effectiveness of use of a personal, self-management, 'smartphone' application (app) to achieve target serum urate concentrations in people with gout. We hypothesise that personalised feedback of serum urate concentrations will improve adherence to ULT. Methods and analysis: Setting and design: Primary care. A prospective, cluster randomised (by general practitioner (GP) practices), controlled trial. Participants: GP practices will be randomised to either intervention or control clusters with their patients allocated to the same cluster. Intervention: The intervention group will have access to the Healthy.me app tailored for the self-management of gout. The control group patients will have access to the same app modified to remove all functions except the Gout Attack Diary. Primary and secondary outcomes: The proportion of patients whose serum urate concentrations are less than or equal to 0.36 mmol/L after 6 months. Secondary outcomes will be proportions of patients achieving target urate concentrations at 12 months, ULT adherence rates, serum urate concentrations at 6 and 12 months, rates of attacks of gout, quality of life estimations and process and economic evaluations. The study is designed to detect a ≥30% improvement in the intervention group above the expected 50% achievement of target serum urate at 6 months in the control group: power 0.80, significance level 0.05, assumed 'dropout' rate 20%. Ethics and dissemination: This study has been approved by the University of New South Wales Human Research Ethics Committee. Study findings will be disseminated in international conferences and peer-reviewed journal. Trial registration number: ACTRN12616000455460 .